Canine Scent Detection and Microbial Source Tracking of Human Waste Contamination in Storm Drains. (1st June 2014) - Van De Werfhorst, Laurie C.; Murray, Jill L.S.; Reynolds, Scott; Reynolds, Karen; Holden, Patricia A.
ABSTRACT: : Human fecal contamination of surface waters and drains is difficult to diagnose. DNA‐based and chemical analyses of water samples can be used to specifically quantify human waste contamination, but their expense precludes routine use. We evaluated canine scent tracking, using two dogs trained to respond to the scent of municipal wastewater, as a field approach for surveying human fecal contamination. Fecal indicator bacteria, as well as DNA‐based and chemical markers of human waste, were analyzed in waters sampled from canine scent‐evaluated sites (urban storm drains and creeks). In the field, the dogs responded positively (70% and 100%) at sites for which sampled waters were then confirmed as contaminated with human waste. When both dogs indicated a negative response, human waste markers were absent. Overall, canine scent tracking appears useful for prioritizing sampling sites for which DNA‐based and similarly expensive assays can confirm and quantify human waste contamination.